German capitalism: Does it exist? Can it survive? - Wolfgang Streeck (Max-Planck-Institut für Gesellschaftsforschung, 1995)
Drawing on extensive comparison with the United States, Japan and Britain, the paper describes the "German model" of advanced capitalism as an institutionalized high-wage economy combining high competitiveness in world markets with strong social cohesion and, in particular, low levels of inequality along a variety of dimensions. This combination is explained by a unique set of socio-economic institutions, in particular socially instituted and circumscribed markets, negotiated firms commanding long-term attachment of both labor and capital, a facilitating state relying mainly on indirect means of intervention, widespread associational self-governance by organized groups in civil society, and institutionalized cultural patterns that promote long-term commitments and continuity. These institutions are shown to call forth and support a particular pattern of production, sometimes referred to as diversified quality production, that has in the 1970s and 1980s made possible both high wages and a low dispersion of wages and incomes. In its second part, the paper proceeds to analyze in detail the performance problems of an institutionalized high-wage economy of the German kind, and specifies a set of conditions that must be met for such an economy to remain simultaneously competitive and socially cohesive. The present crisis of the German "social market economy" is discussed in terms of a coincidence of three factors: a possible secular exhaustion of the model as such, the shock of unification, and the constraints imposed by growing globalization of the capitalist economy on national economic governance. – – Auf der Grundlage eines Vergleichs mit den Vereinigten Staaten, Japan und Großbritannien wird das "deutsche Modell" des entwickelten Kapitalismus als institutionalisierte Hochlohnwirtschaft beschrieben, die hohe Wettbewerbsfähigkeit in internationalen Märkten mit starker sozialer Kohäsion und relativ geringer wirtschaftlicher Ungleichheit verbindet. Diese Kombination wird als Resultat einer Reihe typischer sozio-ökonomischer Institutionen erklärt, insbesondere sozial institutionalisierter und umschriebener Märkte; durch Aushandlung regierter Unternehmen, deren Kapital und Arbeit langfristig an sie gebunden sind; einen unterstützenden Staat, der sich vornehmlich indirekter Interventionsformen bedient; weitverbreiteter verbandlicher Selbstregulierung organisierter gesellschaftlicher Gruppen; und institutionalisierter kultureller Muster, die langfristige Bindungen und Kontinuität fördern. Diese Institutionen begründen und unterstützen eine bestimmte Art wirtschaftlicher Produktion, die als diversifizierte Qualitätsproduktion bezeichnet worden ist und in den siebziger und achtziger Jahren zugleich hohe Löhne und eine geringe Dispersion von Löhnen und Einkommen ermöglicht hat. In seinem zweiten Teil untersucht der Aufsatz die derzeitigen Bestandsprobleme einer institutionalisierten Hochlohnökonomie der deutschen Art und nennt eine Reihe von Bedingungen, die erfüllt sein müssen, damit eine solche Ökonomie zugleich wettbewerbsfähig und sozial kohäsionsfähig bleiben kann. Die gegenwärtige Krise der deutschen "sozialen Marktwirtschaft" wird als Resultat des Zusammentreffens dreier Faktoren dargestellt: einer möglichen säkularen Erschöpfung des Modells als solchem, des Schocks der Wiedervereinigung, und der Rückwirkungen der zunehmenden Globalisierung der kapitalistischen Ökonomie auf nationale Formen wirtschaftlicher Steuerung.
Keywords: 300